Enhancing magnetoimpedance response by anisotropic surface-charge accumulation - Zare, Mohammad; Jamilpanah, Loghman; Sadeghi, Ali; Ghanaatshoar, Majid; Mohseni, Majid (Journal of magnetism and magnetic materials, 2024)
•Surface-charge engineering via near-field electrospinning enhances Magnetoimpedance (MI) response.•Interface alignment of fibers influences the ferroelectric/ferromagnetic interaction, impacting MI response.•The anisotropic TiO2/PVA/CTAB composite fibers generate single-peak MI patterns in Co-based ribbons.•NFES-produced surface charges underpin a potential avenue for magnetic material modification in flexible magnetoelectric devices. Magnetoimpedance (MI) elements show potential application in detection devices as well as advanced electronic components such as neuro-morphing computing and magneto-ionics. We demonstrate surface-charge accumulation via the transformative impact of near-field electrospinning on MI response of Co-based ribbons via longitudinal or transverse formation of aligned TiO2/PVA/CTAB composite fibers. MI represents sensitivity changes against anisotropic charge accumulation designed at the surface via longitudinally or transversely grown fibers. Notably, MI for the longitudinal electrospun exhibits a unique single-peak pattern, in contrast to the conventional dual-peak behavior. This variation is attributed to the meticulous alignment of fibers along the length and width of the ribbons, triggering a dynamic interplay at the crucial ferroelectric/ferromagnetic interface. Our finding demonstrates MI response control through interacting with anisotropic-order of surface-charge mediated by composite fibers.